1984
DOI: 10.1113/jphysiol.1984.sp015056
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of parallel neutral amino acid transport systems in the basolateral membrane of cat salivary epithelium.

Abstract: SUMMARY1. Transport of short-chain and long-chain neutral amino acids across the basolateral membrane of the epithelium in the perfused cat salivary gland has been studied using a rapid (< 30 s) single circulation paired-tracer dilution technique. Amino acid uptake was measured by comparing the venous dilution profiles for a tritiated amino acid and D-[14C]mannitol (extracellular reference) following a bolus intra-arterial injection of a mixture containing both molecules. Unidirectional influx (v) was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Other features of L-leucine transport revealed a maximal acceleration of tracer efflux by low concentrations of extracellular L-leucine (see Tables 1 and 2), a phenomenon observed previously in the perfused salivary gland and pancreas (Mann & Yudilevich, 1984;Mann & Peran, 1986). We also noted that, unlike most amino acids, L-methionine and D-leucine were potent inhibitors of tracer efflux (Fig.…”
Section: Endothelial Cell Removal Of Serotonin and Dopaminementioning
confidence: 58%
See 1 more Smart Citation
“…Other features of L-leucine transport revealed a maximal acceleration of tracer efflux by low concentrations of extracellular L-leucine (see Tables 1 and 2), a phenomenon observed previously in the perfused salivary gland and pancreas (Mann & Yudilevich, 1984;Mann & Peran, 1986). We also noted that, unlike most amino acids, L-methionine and D-leucine were potent inhibitors of tracer efflux (Fig.…”
Section: Endothelial Cell Removal Of Serotonin and Dopaminementioning
confidence: 58%
“…Endothelial cell transport was measured using a rapid dual-isotope dilution technique (Yudilevich & Mann, 1982) previously employed for amino acid transport studies in the perfused salivary gland and pancreas (see Mann & Yudilevich, 1984;Norman & Mann, 1987). After a 45-60 min equilibration period with an amino acid-free perfusate endothelial cell columns were challenged (150,l in 30 s) with a tritiated (7,uCi) Fig.…”
Section: Measurement Of Endothelial Cell Transportmentioning
confidence: 99%
“…Previous paired-tracer dilution studies (see of amino acid transport systems present in the basolateral membrane of the cat salivary epithelium have revealed that the influx of small and large neutral amino acids was mediated by two separate carriers (Bustamante, Mann & Yudilevich, 1981;Mann & Yudilevich, 1984). This epithelium readily takes up L-lysine (Mann & Yudilevich, 1984) and earlier cross-inhibition experiments performed in vivo (Bustamante et at.…”
Section: Introductionmentioning
confidence: 99%
“…This epithelium readily takes up L-lysine (Mann & Yudilevich, 1984) and earlier cross-inhibition experiments performed in vivo (Bustamante et at. 1981) showed that L-lysine had no affinity for the neutral transport systems ASC (alanineserine-cysteine preferring) and L (leucine preferring).…”
Section: Introductionmentioning
confidence: 99%
“…lactate) transport at the sarcolemmal membrane of the rabbit heart , we chose to quantify noradrenaline uptake relative to D-mannitol, an extracellular tracer of similar size and diffusibility. This approach in the heart resembles the analysis used to evaluate cellular uptake in organs with fenestrated capillaries such as the salivary gland (Bustamante et al 1981;Mann, Tradatti & Yudilevich, 1982;Mann & Yudilevich, 1984), in which transcapillary exchange of small solutes was shown to be flow limited (Mann, Smaje & Yudilevich, 1979).…”
Section: Transcapillary Exchange Of D-mannitol and L-noradrenalinementioning
confidence: 99%